Genetic algorithms and remote sensing technology for tracking flight debris - Marghany, Maged (Advances in mechatronics and mechanical engineering (AMME) book series., 2020)
"This book explores the use of genetic algorithms in the context of the analysis of remotely sensed images. This is illustrated with a case study of the M370 crash"--